Population dynamics of Chrysomya megacephala (Diptera : Calliphoridae) at different temperatures - Silva, ICR; Godoy, WAC; Von Zuben, C. J.; Mancera, PFA (Entomological Soc Southern Africa, 2004)
In this study we analysed the theoretical population dynamics of C. megacephala, an exotic blowfly, kept at 25 and 30degreesC, using a density-dependent mathematical model, with parametric estimates of survival and fecundity in the laboratory. No change in terms of oscillation patterns was found for the two temperatures. The populations exhibited a two-point limit cycle, i.e. oscillations between two fixed points, at 25 and 30degreesC. However a quantitative change was observed, indicating that at 25degreesC the number of immatures in equilibrium is 1176 and at 30degreesC, 1944. The implications of this difference in terms of equilibrium for population dynamics of C. megacephala are discussed.
Keywords: population dynamics; Chrysomya megacephala; mathematical model; competition; temperatures